Wear-resistant large-size dust removal and denitration integrated filter element and preparation method thereof
By using stainless steel frames and metal grid structures in ceramic fiber membrane materials, combining hot melt composite technology and nanoparticle fixation catalyst methods, the problems of poor wear resistance and length limitation of ceramic fiber membrane materials are solved, and efficient dust removal, denitrification and solid waste reuse are achieved.
Patent Information
- Application Number
- CN202411887498.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-14
AI Technical Summary
The existing ceramic fiber membrane materials have poor wear resistance during use, short service life, and limited length. The flange compressive strength is insufficient, it is easy to break and cannot be recycled.
Stainless steel is used as the skeleton of the filter element, and the wear resistance and compressive strength of the outer wall of the tube are improved through metal grid and hot melt composite technology, and the treated functional ceramic fiber membrane material waste and cationic nanoparticles are added to the preparation method to achieve solid waste reuse and efficient fixation of catalysts.
It significantly improves the service life of the filter element, avoids the fracture problem at the flange connection, realizes the reuse of the ceramic fiber membrane material after use, reduces the cost of raw materials, and reduces environmental pollution.
Smart Images

Figure CN119607723A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of filter element preparation, and in particular to a wear-resistant large-size dust removal and denitrification integrated filter element and a preparation method thereof. Background Art
[0002] In the cement industry, the traditional method is to use filter bags and honeycombs for dust removal and denitrification. Later, due to the increase in temperature resistance requirements, metal ceramic membranes replaced non-temperature-resistant filter bags and were optimized to metal membranes and honeycombs. In order to further reduce operating and construction costs, in recent years, the cement industry has begun to use integrated ceramic fiber membrane materials for dust removal and denitrification as filter elements to remove dust and nitrogen oxides. Due to the good high temperature resistance and high filtration efficiency of integrated ceramic fiber membrane materials for dust removal and denitrification, it has become the development trend of filter materials for dust removal and denitrification. However, there are some problems in the actual application process, which limit the service life of integrated ceramic fiber membrane materials for dust removal and denitrification. Specifically: First, the wear resistance of the surface of the ceramic fiber membrane material is poor and the service life is short; second, the current ceramic fiber membrane material is short, mainly 3m in length. After increasing the length of the ceramic fiber membrane material, the compressive strength of the flange cannot meet the use requirements, and it is easy to break during installation and use, resulting in the ceramic fiber membrane material after use cannot be reused. Summary of the invention
[0003] In view of the shortcomings of the prior art, the present invention provides a wear-resistant large-size integrated dust removal and denitrification filter element and a preparation method, which can be used to prepare a large-size integrated dust removal and denitrification filter element with good wear resistance and high denitrification efficiency, and can also realize the repeated recycling of used ceramic fiber membrane materials.
[0004] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: A wear-resistant large-size integrated dust removal and denitration filter element, comprising: a flange, an aggregate, an outer wall closed end, an inner wall of a tube body, an outer wall of a tube body, a tail structure, and a positioning bolt; The flange is made of one of 304 stainless steel, 210 stainless steel, and 310s stainless steel, with a wall thickness of 4-6 mm and a diameter of 150-240 mm; The aggregate is spherical and filled in the filter element; The closed end of the outer wall is located 10 cm below the flange and is made of one of 304 stainless steel, 210 stainless steel, and 310s stainless steel; The inner wall of the tube body is a metal mesh, made of one of 304 stainless steel, 210 stainless steel, and 310s stainless steel, with a mesh diameter of 0.5 mm and a wire diameter of 0.5-0.8 mm; The outer wall of the tube body is connected to the closed end of the outer wall and is formed by hot-melting composite of two or more layers of metal mesh; When the outer wall of the tube body is formed by hot-melting two layers of metal mesh, the mesh number of the outermost metal mesh is 400-800 mesh, and the mesh number of the innermost metal mesh is 10-100 mesh; When the outer wall of the tube body is formed by hot-melting composite of more than two layers of metal mesh, the mesh number of the outermost layer of metal mesh is 400-800 mesh, the mesh number of the innermost layer of metal mesh is 10-100 mesh, and the mesh number of the middle layer of metal mesh is 100-200 mesh; The outer wall of the tube body is made of a material that is resistant to high temperatures and corrosion; The cross section of the tail structure along the longitudinal direction is semicircular or straight; The filter element has a length of 3-6 meters, an outer diameter of 130-150 mm, and an inner diameter of 90-110 mm.
[0005] A method for preparing the aforementioned wear-resistant large-size integrated dust removal and denitration filter element comprises: preparing a metal skeleton, preparing aggregate, preparing a catalyst slurry, spraying the catalyst slurry, filling and sealing; The metal skeleton is prepared by rolling and welding the inner wall of the tube body, the outer wall of the tube body, and the tail structure. After the outer wall of the tube body and the closed end of the outer wall are welded, the inner wall of the tube body, the outer wall of the tube body, the tail structure, and the closed end of the outer wall are assembled, and positioning bolts are used to ensure that the spacing between the inner wall of the tube body and the outer wall of the tube body is uniform; The aggregate is prepared by uniformly mixing alumina powder, cordierite powder, aluminum silicate chopped fibers, mullite fibers, treated functional ceramic fiber membrane material waste, and cationic nanoparticles, and then uniformly mixing with silica sol to obtain a paste, placing the paste in a filter cartridge with an opening at one end and a periphery of openings with a diameter of 0.3-1.2 mm, wherein a stirring ruler is provided in the middle of the filter cartridge, and the filter cartridge and the stirring ruler rotate in opposite directions, and the rotation speed is 600-1200 rpm, and the paste is squeezed out of the filter cartridge by the extrusion of the stirring ruler, and the extruded paste is thrown out of the filter cartridge by centrifugal force, and then shaped by a rolling ball machine, and then the shaped mud is passed through a drying chamber and dried at 80-120° C. to obtain the aggregate; The alumina powder and cordierite powder have a particle size of 10-100 μm and a purity of more than 98%; The specific gram value of the aluminum silicate chopped fibers is 50-100 mL / 20 g; The specific gram value of the mullite fiber is 30-80mL / 20g; The weight ratio of the alumina powder, cordierite powder, aluminum silicate chopped fibers, mullite fibers, treated functional ceramic fiber membrane material waste, cationic nanoparticles, and silica sol is 0-50:0-50:0-50:0-50:30-100:4-5:60-200; The preparation method of the treated functional ceramic fiber membrane material waste is as follows: cleaning the dust on the surface of the used functional ceramic fiber membrane material waste, then grinding it with sandpaper, controlling the grinding thickness to be 1 mm, cleaning the dust on the surface, adding it into a ball mill for ball milling, and then passing it through a 50-mesh sieve, taking the sieve under, and obtaining the treated functional ceramic fiber membrane material waste; The reduction rate of the denitrification efficiency of the used functional ceramic fiber membrane material waste does not exceed 60%; The catalyst type in the used functional ceramic fiber membrane material waste is one of a vanadium tungsten titanium catalyst and a rare earth catalyst; The preparation method of the cationic nanoparticles comprises the following steps: mixing montmorillonite and a first portion of deionized water, stirring at 50-55° C. for 30-40 minutes, adding a polyvinyl pyrrolidone aqueous solution, continuing stirring for 9-10 hours, centrifuging at 8000-9000 rpm for 14-16 minutes, washing the precipitate with deionized water, mixing with a second portion of deionized water, stirring at 20-40° C. for 30-40 minutes, adding a hexadecyltrimethylammonium bromide aqueous solution, continuing stirring for 4-5 hours, centrifuging at 8000-9000 rpm for 14-16 minutes, washing the precipitate with deionized water, and drying to obtain the cationic nanoparticles; The montmorillonite is sodium montmorillonite with a particle size of 300 nm; The weight ratio of montmorillonite to the first portion of deionized water is 40:1800-2000; The weight ratio of montmorillonite to polyvinyl pyrrolidone aqueous solution is 40:270-290; The weight ratio of montmorillonite to the second portion of deionized water is 40:1400-1700; The weight ratio of montmorillonite to the aqueous solution of hexadecyltrimethylammonium bromide is 40:600-650; The polyvinyl pyrrolidone in the polyvinyl pyrrolidone aqueous solution is polyvinyl pyrrolidone K30, with a mass concentration of 5%; The mass concentration of the aqueous solution of hexadecyltrimethylammonium bromide is 2%; The aggregate has a particle size of 0.2-1 mm and a porosity of 35-70%; The silica sol has a silicon dioxide content of 30-40% and a particle size of 10-50 nm; The catalyst slurry is prepared, wherein the catalyst type in the catalyst slurry is one of a vanadium tungsten titanium catalyst and a rare earth catalyst, and is the same as the catalyst type in the functional ceramic fiber membrane material waste used in the preparation of the treated functional ceramic fiber membrane material waste; When the catalyst type in the catalyst slurry is a vanadium-tungsten-titanium catalyst, the preparation method of the catalyst slurry is to mix titanium dioxide, ammonium metavanadate, ammonium metatungstate, ammonium metamolybdate, silica sol, ammonia water, a surfactant, anionic nanoparticles, and water to obtain a catalyst slurry; The weight ratio of titanium dioxide, ammonium metavanadate, ammonium metatungstate, ammonium metamolybdate, silica sol, ammonia water, surfactant, anionic nanoparticles, and water is 70-75:13-15:9-10:7-8:6-7:18-20:10-11:10-12:90-100; The particle size of the titanium dioxide is 100 nm; The silica sol has a silicon dioxide content of 30-40% and a particle size of 10-50 nm; The mass concentration of the ammonia water is 31%; The surfactant is triethylamine; When the catalyst type in the catalyst slurry is a rare earth catalyst, the preparation method of the catalyst slurry is to mix titanium dioxide, cerium nitrate, a soluble transition metal salt, silica sol, ammonia water, a surfactant, anionic nanoparticles, and water to obtain a catalyst slurry; The weight ratio of titanium dioxide, cerium nitrate, soluble transition metal salt, silica sol, ammonia water, surfactant, anionic nanoparticles, and water is 70-75:15-17:33-35:7-8:20-22:8-10:10-12:120-130; The particle size of the titanium dioxide is 100 nm; The soluble transition metal salt is one or a combination of iron nitrate, manganese nitrate and copper nitrate; The silica sol has a silicon dioxide content of 30-40% and a particle size of 10-50 nm; The mass concentration of the ammonia water is 31%; The surfactant is triethylamine; The preparation method of the anionic nanoparticles in the preparation of the catalyst slurry is as follows: montmorillonite and a first portion of deionized water are mixed, stirred at 50-55° C. for 30-40 minutes, a polyvinyl pyrrolidone aqueous solution is added, stirring is continued for 9-10 hours, centrifuged at 8000-9000 rpm for 14-16 minutes, a precipitate is washed with deionized water, mixed with a second portion of deionized water, stirred at 20-40° C. for 30-40 minutes, a sodium dodecylbenzene sulfonate aqueous solution is added, stirring is continued for 4-5 hours, centrifuged at 8000-9000 rpm for 14-16 minutes, a precipitate is washed with deionized water, and then dried to obtain the anionic nanoparticles; The montmorillonite is sodium montmorillonite with a particle size of 300 nm; The weight ratio of montmorillonite to the first portion of deionized water is 40:1800-2000; The weight ratio of montmorillonite to polyvinyl pyrrolidone aqueous solution is 40:270-290; The weight ratio of montmorillonite to the second portion of deionized water is 40:1400-1700; The weight ratio of montmorillonite to the sodium dodecylbenzene sulfonate aqueous solution is 40:900-1000; The polyvinyl pyrrolidone in the polyvinyl pyrrolidone aqueous solution is polyvinyl pyrrolidone K30, with a mass concentration of 5%; The mass concentration of the sodium dodecylbenzenesulfonate aqueous solution is 1%; The spraying catalyst slurry dilutes the catalyst slurry to a solid content of 5-7% to obtain a diluted catalyst slurry; the diluted catalyst slurry is evenly sprayed on the surface of the aggregate, the mass ratio of the diluted catalyst slurry to the aggregate is controlled to be 1-2:1, after drying at 80-150°C, calcined at 450-550°C for 5-6h to obtain a catalyst-loaded aggregate; The loading method is to load the catalyst-loaded aggregate into the area formed by the closed end of the outer wall, the inner wall of the tube body, the outer wall of the tube body, and the tail structure, and then seal it with a flange to obtain a wear-resistant large-size dust removal and denitrification integrated filter element.
[0006] Compared with the prior art, the present invention has the following beneficial effects: (1) The wear-resistant large-size integrated dust removal and denitrification filter element of the present invention uses stainless steel as the skeleton of the filter element, which can significantly improve the friction of particulate matter on the outer wall during the filtration process and increase the service life of the filter element, thereby avoiding the problem of easy breakage at the connection with the flange. In addition, the lower end of the flange in the filter element is added with an outer wall closed end, which can solve the problem of poor operating effect caused by the different expansion coefficients of metal and ceramic under high temperature conditions.
[0007] (2) The preparation method of the wear-resistant large-size integrated dust removal and denitrification filter element of the present invention can reuse the waste of functional ceramic fiber membrane materials after use, which can reduce the cost of raw materials, realize the recycling of solid waste, reduce environmental pollution, and achieve energy conservation and emission reduction; the catalyst adopts a spraying process, which can reduce costs, protect the environment, and reduce pollution; (3) The preparation method of the wear-resistant large-size dust removal and denitrification integrated filter element of the present invention, when preparing the aggregate loaded with catalyst in the filter element, first prepare the aggregate, and when preparing the aggregate, add the treated functional ceramic fiber membrane material waste and cationic nanoparticles, the preparation method of the cationic nanoparticles is first to coat and intercalate montmorillonite with a polyvinyl pyrrolidone aqueous solution, and then to coat and intercalate with a hexadecyltrimethylammonium bromide aqueous solution, so as to insert a mixture of polyvinyl pyrrolidone and hexadecyltrimethylammonium bromide between the layers of montmorillonite, and coat the surface of montmorillonite with micelle aggregates composed of polyvinyl pyrrolidone and hexadecyltrimethylammonium bromide to obtain cationic nanoparticles, the micelle aggregates on the surface of the cationic nanoparticles can fix and coat the catalyst desorbed from the treated functional ceramic fiber membrane material waste, and can also play a role in stabilizing and dispersing the silica sol in the preparation of the aggregate, and in the spraying of the catalyst When calcining in the catalyst slurry, polyvinyl pyrrolidone and hexadecyltrimethylammonium bromide form a porous substance after calcination, thereby increasing the specific surface area of the desorbed catalyst; anionic nanoparticles are added in the preparation of the catalyst slurry, and the preparation method of the anionic nanoparticles is to first coat and intercalate montmorillonite with an aqueous solution of polyvinyl pyrrolidone, and then coat and intercalate with an aqueous solution of sodium dodecylbenzene sulfonate, thereby inserting a mixture of polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate between the layers of montmorillonite, and coating the surface of the montmorillonite with micelle aggregates composed of polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate to obtain anionic nanoparticles, and the micelle aggregates on the surface of the anionic nanoparticles can coat the catalytic active components, and can also play a role in stabilizing and dispersing silica sol in the preparation of aggregates. In addition, the electrostatic effect between the anionic nanoparticles and the cationic nanoparticles in the aggregates can also improve the binding force between the catalyst slurry and the aggregates; (4) The preparation method of the wear-resistant large-size integrated dust removal and denitrification filter element of the present invention, the dust removal efficiency of the prepared wear-resistant large-size integrated dust removal and denitrification filter element is 99.1-99.7%, at an air velocity of 4000h -1 , NO X When the concentration is 1000ppm, the denitrification efficiency is 91.4-92.3% at 220℃ and 95.7-98.0% at 450℃. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] Figure 1 This is a structural diagram of a wear-resistant large-size integrated dust removal and denitration filter element of Example 1; In the figure: 1-flange; 2-aggregate; 3-closed end of outer wall; 4-inner wall of tube body; 5-outer wall of tube body; 6-tail structure; 7-locating bolt. DETAILED DESCRIPTION
[0009] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.
[0010] Example 1 Depend on Figure 1 As shown, a wear-resistant large-size integrated dust removal and denitrification filter element comprises: a flange 1, an aggregate 2, an outer wall closed end 3, a tube body inner wall 4, a tube body outer wall 5, a tail structure 6, and a positioning bolt 7; The flange 1 is made of 304 stainless steel, with a wall thickness of 4 mm and a diameter of 150 mm; The aggregate 2 is spherical and filled in the filter element; The outer wall closed end 3 is located 10 cm below the flange and is made of 304 stainless steel; The inner wall 4 of the tube body is a metal mesh made of 304 stainless steel, with a mesh diameter of 0.5 mm and a wire diameter of 0.5 mm; The outer wall 5 of the tube body is connected to the closed end 3 of the outer wall, and is formed by hot-melting two layers of metal mesh, the mesh number of the outermost layer of the metal mesh is 400 mesh, and the mesh number of the innermost layer of the metal mesh is 10 mesh; The outer wall 5 of the tube body is made of 304 stainless steel; The cross section of the tail structure 6 along the longitudinal direction is semicircular; The filter element has a length of 3 meters, an outer diameter of 130 mm and an inner diameter of 90 mm.
[0011] A method for preparing the aforementioned wear-resistant large-size integrated dust removal and denitrification filter element comprises: preparing a metal skeleton, preparing aggregates, preparing a catalyst slurry, spraying the catalyst slurry, filling and sealing. Specifically: 1. Prepare the metal skeleton: Figure 1 , prepare the inner wall 4 of the tube body, the outer wall 5 of the tube body, and the tail structure 6 by rolling and welding, weld the outer wall 5 of the tube body to the outer wall closed end 3, assemble the inner wall 4 of the tube body, the outer wall 5 of the tube body, the tail structure 6, and the outer wall closed end 3, and use the positioning bolt 7 to ensure that the spacing between the inner wall 4 of the tube body and the outer wall 5 of the tube body is uniform; 2. Preparation of aggregate: The treated functional ceramic fiber membrane material waste and cationic nanoparticles are mixed evenly, and then mixed evenly with silica sol to obtain a paste. The paste is placed in a filter cartridge with an opening at one end and a hole around it with a diameter of 0.3 mm. There is a stirring ruler in the middle of the filter cartridge. The filter cartridge and the stirring ruler rotate in opposite directions, and the speed is 600 rpm. The paste is squeezed out of the filter cartridge by the extrusion of the stirring ruler, and the extruded paste is thrown out of the filter cartridge by centrifugal force, and then shaped by a rolling ball machine, and then the shaped mud is passed through a drying chamber and dried at 80°C to obtain aggregate; The alumina powder and cordierite powder have a particle size of 10 μm and a purity of 98.5%; The specific gram value of the aluminum silicate chopped fibers is 50 mL / 20 g; The specific gram value of the mullite fiber is 30mL / 20g; The weight ratio of the treated functional ceramic fiber membrane material waste, cationic nanoparticles, and silica sol is 100:5:60; The preparation method of the treated functional ceramic fiber membrane material waste is as follows: cleaning the dust on the surface of the used functional ceramic fiber membrane material waste, then grinding it with sandpaper, controlling the grinding thickness to be 1 mm, cleaning the dust on the surface, adding it into a ball mill for ball milling, and then passing it through a 50-mesh sieve, taking the sieve under, and obtaining the treated functional ceramic fiber membrane material waste; The reduction rate of the denitrification efficiency of the used functional ceramic fiber membrane material waste is 55%, which meets the judgment standard of not more than 60%; The catalyst type in the used functional ceramic fiber membrane material waste is a vanadium tungsten titanium catalyst; The preparation method of the cationic nanoparticles is as follows: montmorillonite and a first portion of deionized water are mixed, stirred at 50° C. for 30 minutes, a polyvinyl pyrrolidone aqueous solution is added, stirring is continued for 9 hours, centrifuged at 8000 rpm for 14 minutes, a precipitate is washed with deionized water, mixed with a second portion of deionized water, stirred at 20° C. for 30 minutes, a hexadecyltrimethylammonium bromide aqueous solution is added, stirring is continued for 4 hours, centrifuged at 8000 rpm for 14 minutes, a precipitate is washed with deionized water, and then dried to obtain cationic nanoparticles; The montmorillonite is sodium montmorillonite with a particle size of 300 nm; The weight ratio of montmorillonite to the first portion of deionized water was 40:1800; The weight ratio of montmorillonite to polyvinyl pyrrolidone aqueous solution is 40:270; The weight ratio of montmorillonite to the second portion of deionized water is 40:1400; The weight ratio of montmorillonite to the aqueous solution of hexadecyltrimethylammonium bromide is 40:600; The polyvinyl pyrrolidone in the polyvinyl pyrrolidone aqueous solution is polyvinyl pyrrolidone K30, with a mass concentration of 5%; The mass concentration of the aqueous solution of hexadecyltrimethylammonium bromide is 2%; The aggregate has a particle size of 0.2 mm and a porosity of 35%; The silica sol has a silicon dioxide content of 30% and a particle size of 10 nm; 3. Prepare catalyst slurry: The catalyst type in the catalyst slurry is the same as the catalyst type in the functional ceramic fiber membrane material waste used in the preparation of the functional ceramic fiber membrane material waste treated in the aggregate preparation in step 2, which is also a vanadium tungsten titanium catalyst. The preparation method of the catalyst slurry is: titanium dioxide, ammonium metavanadate, ammonium metatungstate, ammonium metamolybdate, silica sol, ammonia water, surfactant, anion nanoparticles, and water are mixed to obtain a catalyst slurry; The weight ratio of titanium dioxide, ammonium metavanadate, ammonium metatungstate, ammonium metamolybdate, silica sol, ammonia water, surfactant, anionic nanoparticles, and water is 70:13:9:7:6:18:10:10:90; The particle size of the titanium dioxide is 100 nm; The silica sol has a silicon dioxide content of 30% and a particle size of 10 nm; The mass concentration of the ammonia water is 31%; The surfactant is triethylamine; The preparation method of the anionic nanoparticles in the preparation of the catalyst slurry is as follows: montmorillonite and a first portion of deionized water are mixed, stirred at 50° C. for 30 minutes, a polyvinyl pyrrolidone aqueous solution is added, stirring is continued for 9 hours, centrifuged at 8000 rpm for 14 minutes, a precipitate is washed with deionized water, mixed with a second portion of deionized water, stirred at 20° C. for 30 minutes, a sodium dodecylbenzene sulfonate aqueous solution is added, stirring is continued for 4 hours, centrifuged at 8000 rpm for 14 minutes, a precipitate is washed with deionized water, and then dried to obtain anionic nanoparticles; The montmorillonite is sodium montmorillonite with a particle size of 300 nm; The weight ratio of montmorillonite to the first portion of deionized water was 40:1800; The weight ratio of montmorillonite to polyvinyl pyrrolidone aqueous solution is 40:270; The weight ratio of montmorillonite to the second portion of deionized water is 40:1400; The weight ratio of montmorillonite to the aqueous solution of sodium dodecylbenzene sulfonate is 40:900; The polyvinyl pyrrolidone in the polyvinyl pyrrolidone aqueous solution is polyvinyl pyrrolidone K30, with a mass concentration of 5%; The mass concentration of the sodium dodecylbenzenesulfonate aqueous solution is 1%; 4. Spraying catalyst slurry: dilute the catalyst slurry to a solid content of 5% to obtain a diluted catalyst slurry; spray the diluted catalyst slurry evenly on the surface of the aggregate, control the mass ratio of the diluted catalyst slurry to the aggregate to be 1:1, dry at 80°C, and calcine at 450°C for 5h to obtain a catalyst-loaded aggregate; 5. Loading: The catalyst-loaded aggregate is loaded into the area formed by the outer wall closed end 3, the inner wall 4 of the tube body, the outer wall 5 of the tube body, and the tail structure 6, and then sealed with the flange 1 to obtain a wear-resistant large-size dust removal and denitrification integrated filter element.
[0012] The dust removal efficiency of the wear-resistant large-size dust removal and denitrification integrated filter element prepared in this embodiment is 99.1%. -1 , NO X When the concentration is 1000ppm, the denitrification efficiency is 91.4% at 220℃ and 95.7% at 450℃.
[0013] Example 2 A wear-resistant large-size integrated dust removal and denitration filter element, comprising: a flange 1, an aggregate 2, an outer wall closed end 3, an inner wall of a pipe body 4, an outer wall of a pipe body 5, a tail structure 6, and a positioning bolt 7; The flange 1 is made of 210 stainless steel, with a wall thickness of 5 mm and a diameter of 200 mm; The aggregate 2 is spherical and filled in the filter element; The outer wall closed end 3 is located 10 cm below the flange and is made of 210 stainless steel; The inner wall 4 of the tube body is a metal mesh made of 210 stainless steel, with a mesh diameter of 0.5 mm and a wire diameter of 0.6 mm; The outer wall 5 of the tube body is connected to the closed end 3 of the outer wall, and is formed by hot-melting three layers of metal mesh; the mesh number of the outermost layer of metal mesh is 500 mesh, the mesh number of the innermost layer of metal mesh is 50 mesh, and the mesh number of the middle layer of metal mesh is 150 mesh; The outer wall 5 of the tube body is made of 210 stainless steel; The cross section of the tail structure 6 along the longitudinal direction is semicircular; The filter element has a length of 5 meters, an outer diameter of 150 mm and an inner diameter of 110 mm.
[0014] A method for preparing the aforementioned wear-resistant large-size integrated dust removal and denitrification filter element comprises: preparing a metal skeleton, preparing aggregates, preparing a catalyst slurry, spraying the catalyst slurry, filling and sealing. Specifically: 1. Prepare the metal skeleton: prepare the inner wall 4, outer wall 5 and tail structure 6 of the tube body by rolling and welding, weld the outer wall 5 and the closed end 3 of the outer wall, assemble the inner wall 4, outer wall 5, tail structure 6 and the closed end 3 of the outer wall, and use the positioning bolt 7 to ensure that the spacing between the inner wall 4 and the outer wall 5 of the tube body is uniform; 2. Prepare aggregate: Alumina powder, cordierite powder, aluminum silicate chopped fibers, mullite fibers, treated functional ceramic fiber membrane material waste, and cationic nanoparticles are mixed evenly, and then mixed evenly with silica sol to obtain a paste. The paste is placed in a filter cartridge with an opening at one end and a hole with a diameter of 1 mm around it. There is a stirring ruler in the middle of the filter cartridge. The filter cartridge and the stirring ruler rotate in opposite directions, and the speed is 1000 rpm. The paste is squeezed out of the filter cartridge by the extrusion of the stirring ruler, and the extruded paste is thrown out of the filter cartridge by centrifugal force, and then shaped by a rolling ball machine, and then the shaped mud is passed through a drying chamber and dried at 100°C to obtain aggregate; The alumina powder and cordierite powder have a particle size of 50 μm and a purity of 99%; The specific gram value of the aluminum silicate chopped fibers is 80 mL / 20 g; The specific gram value of the mullite fiber is 50mL / 20g; The weight ratio of the alumina powder, cordierite powder, aluminum silicate chopped fibers, mullite fibers, treated functional ceramic fiber membrane material waste, cationic nanoparticles, and silica sol is 20:20:20:20:60:5:130; The preparation method of the treated functional ceramic fiber membrane material waste is as follows: cleaning the dust on the surface of the used functional ceramic fiber membrane material waste, then grinding it with sandpaper, controlling the grinding thickness to be 1 mm, cleaning the dust on the surface, adding it into a ball mill for ball milling, and then passing it through a 50-mesh sieve, taking the sieve under, and obtaining the treated functional ceramic fiber membrane material waste; The reduction rate of the denitrification efficiency of the used functional ceramic fiber membrane material waste is 55%, which meets the judgment standard of not more than 60%; The catalyst type in the used functional ceramic fiber membrane material waste is a rare earth catalyst; The preparation method of the cationic nanoparticles is as follows: montmorillonite and a first portion of deionized water are mixed, stirred at 52° C. for 35 minutes, a polyvinyl pyrrolidone aqueous solution is added, stirring is continued for 9.5 hours, centrifuged at 9000 rpm for 15 minutes, a precipitate is washed with deionized water, mixed with a second portion of deionized water, stirred at 30° C. for 35 minutes, a hexadecyltrimethylammonium bromide aqueous solution is added, stirring is continued for 4.5 hours, centrifuged at 9000 rpm for 15 minutes, a precipitate is washed with deionized water, and then dried to obtain cationic nanoparticles; The montmorillonite is sodium montmorillonite with a particle size of 300 nm; The weight ratio of montmorillonite to the first portion of deionized water was 40:1900; The weight ratio of montmorillonite to polyvinyl pyrrolidone aqueous solution is 40:280; The weight ratio of montmorillonite to the second portion of deionized water is 40:1600; The weight ratio of montmorillonite to the aqueous solution of hexadecyltrimethylammonium bromide is 40:620; The polyvinyl pyrrolidone in the polyvinyl pyrrolidone aqueous solution is polyvinyl pyrrolidone K30, with a mass concentration of 5%; The mass concentration of the aqueous solution of hexadecyltrimethylammonium bromide is 2%; The aggregate has a particle size of 0.5 mm and a porosity of 70%; The silica sol has a silicon dioxide content of 30% and a particle size of 20 nm; 3. Prepare catalyst slurry: the catalyst type in the catalyst slurry is the same as the catalyst type in the functional ceramic fiber membrane material waste used in the preparation of the functional ceramic fiber membrane material waste treated in the aggregate preparation in step 2, the catalyst type in the catalyst slurry is a rare earth catalyst, and the catalyst slurry is prepared by mixing titanium dioxide, cerium nitrate, a soluble transition metal salt, silica sol, ammonia water, a surfactant, anionic nanoparticles, and water to obtain a catalyst slurry; The weight ratio of titanium dioxide, cerium nitrate, soluble transition metal salt, silica sol, ammonia water, surfactant, anionic nanoparticles, and water is 72:16:34:7.5:21:9:11:125; The particle size of the titanium dioxide is 100 nm; The soluble transition metal salt is a combination of ferric nitrate and manganese nitrate, wherein the mass ratio of ferric nitrate to manganese nitrate is 1:1; The silica sol has a silicon dioxide content of 30% and a particle size of 20 nm; The mass concentration of the ammonia water is 31%; The surfactant is triethylamine; The preparation method of the anionic nanoparticles in the preparation of the catalyst slurry is as follows: montmorillonite and a first portion of deionized water are mixed, stirred at 52° C. for 35 minutes, a polyvinyl pyrrolidone aqueous solution is added, stirring is continued for 9.5 hours, centrifuged at 9000 rpm for 15 minutes, a precipitate is washed with deionized water, mixed with a second portion of deionized water, stirred at 30° C. for 35 minutes, a sodium dodecylbenzene sulfonate aqueous solution is added, stirring is continued for 4.5 hours, centrifuged at 9000 rpm for 15 minutes, a precipitate is washed with deionized water, and then dried to obtain anionic nanoparticles; The montmorillonite is sodium montmorillonite with a particle size of 300 nm; The weight ratio of montmorillonite to the first portion of deionized water was 40:1900; The weight ratio of montmorillonite to polyvinyl pyrrolidone aqueous solution is 40:280; The weight ratio of montmorillonite to the second portion of deionized water is 40:1500; The weight ratio of montmorillonite to the aqueous solution of sodium dodecylbenzene sulfonate is 40:950; The polyvinyl pyrrolidone in the polyvinyl pyrrolidone aqueous solution is polyvinyl pyrrolidone K30, with a mass concentration of 5%; The mass concentration of the sodium dodecylbenzenesulfonate aqueous solution is 1%; 4. Spraying catalyst slurry: dilute the catalyst slurry to a solid content of 6% to obtain a diluted catalyst slurry; spray the diluted catalyst slurry evenly on the surface of the aggregate, control the mass ratio of the diluted catalyst slurry to the aggregate to be 2:1, dry at 120°C, and calcine at 500°C for 5.5h to obtain a catalyst-loaded aggregate; 5. Loading: The catalyst-loaded aggregate is loaded into the area formed by the outer wall closed end 3, the inner wall 4 of the tube body, the outer wall 5 of the tube body, and the tail structure 6, and then sealed with the flange 1 to obtain a wear-resistant large-size dust removal and denitrification integrated filter element.
[0015] The dust removal efficiency of the wear-resistant large-size dust removal and denitrification integrated filter element prepared in this embodiment is 99.7%. -1 , NO X When the concentration is 1000ppm, the denitrification efficiency is 92.1% at 220℃ and 97.8% at 450℃.
[0016] Example 3 A wear-resistant large-size integrated dust removal and denitration filter element, comprising: a flange 1, an aggregate 2, an outer wall closed end 3, an inner wall of a pipe body 4, an outer wall of a pipe body 5, a tail structure 6, and a positioning bolt 7; The flange 1 is made of 310s stainless steel, with a wall thickness of 6 mm and a diameter of 240 mm; The aggregate 2 is spherical and filled in the filter element; The outer wall closed end 3 is located 10 cm below the flange and is made of 310s stainless steel; The inner wall 4 of the tube body is a metal mesh made of 310s stainless steel, with a mesh diameter of 0.5mm and a wire diameter of 0.8mm; The outer wall 5 of the tube body is connected to the closed end 3 of the outer wall, and is formed by compounding four layers of metal meshes by hot melting; the mesh number of the outermost layer of metal mesh is 800 meshes, the mesh number of the innermost layer of metal mesh is 100 meshes, and the mesh numbers of the two middle layers of metal meshes are 200 meshes; The outer wall 5 of the tube body is made of 310s stainless steel; The cross section of the tail structure 6 along the longitudinal direction is a straight line; The filter element has a length of 6 meters, an outer diameter of 150 mm and an inner diameter of 110 mm.
[0017] A method for preparing the aforementioned wear-resistant large-size integrated dust removal and denitrification filter element comprises: preparing a metal skeleton, preparing aggregates, preparing a catalyst slurry, spraying the catalyst slurry, filling and sealing. Specifically: 1. Prepare the metal skeleton: prepare the inner wall 4, outer wall 5 and tail structure 6 of the tube body by rolling and welding, weld the outer wall 5 and the closed end 3 of the outer wall, assemble the inner wall 4, outer wall 5, tail structure 6 and the closed end 3 of the outer wall, and use the positioning bolt 7 to ensure that the spacing between the inner wall 4 and the outer wall 5 of the tube body is uniform; 2. Prepare aggregate: Alumina powder, cordierite powder, aluminum silicate chopped fibers, mullite fibers, treated functional ceramic fiber membrane material waste, and cationic nanoparticles are mixed evenly, and then mixed evenly with silica sol to obtain a paste. The paste is placed in a filter cartridge with an opening at one end and a hole around it with a diameter of 1.2 mm. There is a stirring ruler in the middle of the filter cartridge. The filter cartridge and the stirring ruler rotate in opposite directions, and the speed is 1200 rpm. The paste is squeezed out of the filter cartridge by the extrusion of the stirring ruler, and the extruded paste is thrown out of the filter cartridge by centrifugal force, and then shaped by a rolling ball machine, and then the shaped mud is passed through a drying chamber and dried at 120°C to obtain aggregate; The particle size of the alumina powder and cordierite powder is 100 μm, and the purity is 99%; The specific gram value of the aluminum silicate chopped fibers is 100 mL / 20 g; The specific gram value of the mullite fiber is 80mL / 20g; The weight ratio of the alumina powder, cordierite powder, aluminum silicate chopped fibers, mullite fibers, treated functional ceramic fiber membrane material waste, cationic nanoparticles, and silica sol is 50:50:50:50:100:5:200; The preparation method of the treated functional ceramic fiber membrane material waste is as follows: cleaning the dust on the surface of the used functional ceramic fiber membrane material waste, then grinding it with sandpaper, controlling the grinding thickness to be 1 mm, cleaning the dust on the surface, adding it into a ball mill for ball milling, and then passing it through a 50-mesh sieve, taking the sieve under, and obtaining the treated functional ceramic fiber membrane material waste; The reduction rate of the denitrification efficiency of the used functional ceramic fiber membrane material waste is 55%, which meets the judgment standard of not more than 60%; The catalyst type in the used functional ceramic fiber membrane material waste is a rare earth catalyst; The preparation method of the cationic nanoparticles is as follows: montmorillonite and a first portion of deionized water are mixed, stirred at 55° C. for 40 minutes, a polyvinyl pyrrolidone aqueous solution is added, stirring is continued for 10 hours, centrifuged at 9000 rpm for 16 minutes, a precipitate is washed with deionized water, mixed with a second portion of deionized water, stirred at 40° C. for 40 minutes, a hexadecyltrimethylammonium bromide aqueous solution is added, stirring is continued for 5 hours, centrifuged at 9000 rpm for 16 minutes, a precipitate is washed with deionized water, and then dried to obtain cationic nanoparticles; The montmorillonite is sodium montmorillonite with a particle size of 300 nm; The weight ratio of montmorillonite to the first portion of deionized water was 40:2000; The weight ratio of montmorillonite to polyvinyl pyrrolidone aqueous solution is 40:290; The weight ratio of montmorillonite to the second portion of deionized water is 40:1700; The weight ratio of montmorillonite to the aqueous solution of hexadecyltrimethylammonium bromide is 40:650; The polyvinyl pyrrolidone in the polyvinyl pyrrolidone aqueous solution is polyvinyl pyrrolidone K30, with a mass concentration of 5%; The mass concentration of the aqueous solution of hexadecyltrimethylammonium bromide is 2%; The aggregate has a particle size of 1 mm and a porosity of 70%; The silica sol has a silicon dioxide content of 40% and a particle size of 50 nm; 3. Prepare catalyst slurry: the catalyst type in the catalyst slurry is the same as the catalyst type in the functional ceramic fiber membrane material waste used in the preparation of the functional ceramic fiber membrane material waste treated in the aggregate preparation in step 2, the catalyst type in the catalyst slurry is a rare earth catalyst, and the catalyst slurry is prepared by mixing titanium dioxide, cerium nitrate, a soluble transition metal salt, silica sol, ammonia water, a surfactant, anionic nanoparticles, and water to obtain a catalyst slurry; The weight ratio of titanium dioxide, cerium nitrate, soluble transition metal salt, silica sol, ammonia water, surfactant, anionic nanoparticles, and water is 75:17:35:8:22:10:12:130; The particle size of the titanium dioxide is 100 nm; The soluble transition metal salt is a combination of ferric nitrate, manganese nitrate and copper nitrate, wherein the mass ratio of ferric nitrate, manganese nitrate and copper nitrate is 1:1:1; The silica sol has a silicon dioxide content of 40% and a particle size of 50 nm; The mass concentration of the ammonia water is 31%; The surfactant is triethylamine; The preparation method of the anionic nanoparticles in the preparation of the catalyst slurry is as follows: montmorillonite and a first portion of deionized water are mixed, stirred at 55° C. for 40 minutes, a polyvinyl pyrrolidone aqueous solution is added, stirring is continued for 10 hours, centrifuged at 9000 rpm for 16 minutes, a precipitate is washed with deionized water, mixed with a second portion of deionized water, stirred at 40° C. for 40 minutes, a sodium dodecylbenzene sulfonate aqueous solution is added, stirring is continued for 5 hours, centrifuged at 9000 rpm for 16 minutes, a precipitate is washed with deionized water, and then dried to obtain anionic nanoparticles; The montmorillonite is sodium montmorillonite with a particle size of 300 nm; The weight ratio of montmorillonite to the first portion of deionized water was 40:2000; The weight ratio of montmorillonite to polyvinyl pyrrolidone aqueous solution is 40:290; The weight ratio of montmorillonite to the second portion of deionized water is 40:1700; The weight ratio of montmorillonite to the aqueous solution of sodium dodecylbenzene sulfonate is 40:1000; The polyvinyl pyrrolidone in the polyvinyl pyrrolidone aqueous solution is polyvinyl pyrrolidone K30, with a mass concentration of 5%; The mass concentration of the sodium dodecylbenzenesulfonate aqueous solution is 1%; 4. Spraying catalyst slurry: dilute the catalyst slurry to a solid content of 7% to obtain a diluted catalyst slurry; spray the diluted catalyst slurry evenly on the surface of the aggregate, control the mass ratio of the diluted catalyst slurry to the aggregate to be 2:1, dry at 150°C, and calcine at 550°C for 6h to obtain a catalyst-loaded aggregate; 5. Loading: The catalyst-loaded aggregate is loaded into the area formed by the outer wall closed end 3, the inner wall 4 of the tube body, the outer wall 5 of the tube body, and the tail structure 6, and then sealed with the flange 1 to obtain a wear-resistant large-size dust removal and denitrification integrated filter element.
[0018] The dust removal efficiency of the wear-resistant large-size dust removal and denitrification integrated filter element prepared in this embodiment is 99.6%. -1 , NO X When the concentration is 1000ppm, the denitrification efficiency is 92.3% at 220℃ and 98.0% at 450℃.
[0019] Comparative Example 1 Adjustments are made to the technical solution of Example 2. The specific adjustments are as follows: in the preparation method of the wear-resistant large-size integrated dust removal and denitrification filter element, the addition of cationic nanoparticles in the preparation of aggregate in step 2 is omitted.
[0020] The dust removal efficiency of the wear-resistant large-size dust removal and denitrification integrated filter element prepared in this comparative example is 97.4%. -1 , NO X When the concentration is 1000ppm, the denitrification efficiency is 85.6% at 220℃ and 93.2% at 450℃.
[0021] Comparative Example 2 Adjustments are made to the technical solution of Example 2. The specific adjustments are as follows: in the preparation method of the wear-resistant large-size integrated dust removal and denitrification filter element, the addition of anionic nanoparticles in the preparation of the catalyst slurry in step 3 is omitted.
[0022] The dust removal efficiency of the wear-resistant large-size dust removal and denitrification integrated filter element prepared in this comparative example is 94.3%. -1 , NO X When the concentration is 1000ppm, the denitrification efficiency is 78.1% at 220℃ and 89.4% at 450℃.
[0023] Unless otherwise specified, all percentages used in the present invention are by mass.
[0024] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A wear-resistant large-size integrated dust removal and denitrification filter element, characterized in that: include: Flange (1), aggregate (2), outer wall closed end (3), inner wall of the pipe body (4), outer wall of the pipe body (5), tail structure (6), and positioning bolt (7); The flange (1) is made of one of 304 stainless steel, 210 stainless steel, and 310s stainless steel, with a wall thickness of 4-6 mm and a diameter of 150-240 mm; The aggregate (2) is spherical and filled in the filter element; The closed end (3) of the outer wall is located 10 cm below the flange and is made of one of 304 stainless steel, 210 stainless steel, and 310s stainless steel; The inner wall (4) of the tube body is a metal mesh, made of one of 304 stainless steel, 210 stainless steel, and 310s stainless steel, with a mesh diameter of 0.5 mm and a wire diameter of 0.5-0.8 mm; The outer wall (5) of the tube body is connected to the closed end (3) of the outer wall and is formed by hot-melting composite of two or more layers of metal mesh; The material of the outer wall (5) of the tube body is a high temperature resistant and corrosion resistant material; The tail structure (6) has a cross section in the longitudinal direction that is semicircular or straight; The filter element has a length of 3-6 meters, an outer diameter of 130-150 mm, and an inner diameter of 90-110 mm.
2. The wear-resistant large-size integrated dust removal and denitrification filter element according to claim 1 is characterized in that: When the outer wall (5) of the tube body is formed by combining two layers of metal mesh by hot-melt bonding, the mesh number of the outermost layer of metal mesh is 400-800 meshes, and the mesh number of the innermost layer of metal mesh is 10-100 meshes; When the outer wall (5) of the tube body is formed by hot-melting composite of more than two layers of metal mesh, the mesh number of the outermost layer of metal mesh is 400-800 mesh, the mesh number of the innermost layer of metal mesh is 10-100 mesh, and the mesh number of the middle layer of metal mesh is 100-200 mesh.
3. A method for preparing the wear-resistant large-size integrated dust removal and denitrification filter element according to any one of claims 1 to 2, characterized in that: include: Prepare metal skeleton, prepare aggregate, prepare catalyst slurry, spray catalyst slurry, fill and seal; The metal skeleton is prepared by rolling and welding the inner wall (4) of the tube body, the outer wall (5) of the tube body, and the tail structure (6). After the outer wall (5) of the tube body is welded to the closed end (3) of the outer wall, the inner wall (4) of the tube body, the tail structure (6), and the closed end (3) of the outer wall are assembled, and positioning bolts (7) are used to ensure that the spacing between the inner wall (4) of the tube body and the outer wall (5) of the tube body is uniform; In the preparation of the aggregate, alumina powder, cordierite powder, aluminum silicate chopped fibers, mullite fibers, treated functional ceramic fiber membrane material waste, and cationic nanoparticles are uniformly mixed, and then uniformly mixed with silica sol to obtain a paste, and the paste is pelletized and then dried to obtain the aggregate; The method for preparing the treated functional ceramic fiber membrane material waste is as follows: cleaning the dust on the surface of the used functional ceramic fiber membrane material waste, grinding it, cleaning the dust on the surface, ball milling it, and sieving it to obtain the treated functional ceramic fiber membrane material waste; The catalyst slurry is prepared, wherein the catalyst type in the catalyst slurry is one of a vanadium tungsten titanium catalyst and a rare earth catalyst, and is the same as the catalyst type in the functional ceramic fiber membrane material waste used in the preparation of the treated functional ceramic fiber membrane material waste; The spraying catalyst slurry dilutes the catalyst slurry to a solid content of 5-7% to obtain a diluted catalyst slurry; the diluted catalyst slurry is evenly sprayed on the surface of the aggregate, the mass ratio of the diluted catalyst slurry to the aggregate is controlled to be 1-2:1, after drying at 80-150°C, calcined at 450-550°C for 5-6h to obtain a catalyst-loaded aggregate; The loading method includes loading the catalyst-loaded aggregate into the area formed by the closed end of the outer wall (3), the inner wall of the tube body (4), the outer wall of the tube body (5), and the tail structure (6), and then sealing it with a flange (1) to obtain a wear-resistant large-size dust removal and denitrification integrated filter element.
4. The method for preparing the wear-resistant large-size integrated dust removal and denitrification filter element according to claim 1, characterized in that: In the aggregate preparation, the alumina powder and cordierite powder have a particle size of 10-100 μm and a purity of more than 98%; The specific gram value of the aluminum silicate chopped fibers is 50-100 mL / 20 g; The specific gram value of the mullite fiber is 30-80mL / 20g; The weight ratio of the alumina powder, cordierite powder, aluminum silicate chopped fibers, mullite fibers, treated functional ceramic fiber membrane material waste, cationic nanoparticles, and silica sol is 0-50:0-50:0-50:0-50:30-100:4-5:60-200; The ball forming process comprises placing the paste material in a filter cartridge which is open at one end and surrounded by holes with a diameter of 0.3-1.2 mm. A stirring ruler is arranged in the middle of the filter cartridge. The filter cartridge and the stirring ruler rotate in opposite directions at a speed of 600-1200 rpm. The paste material is squeezed out of the filter cartridge by the extrusion of the stirring ruler, and the extruded paste material is thrown out of the filter cartridge by centrifugal force, and then shaped by a ball rolling machine.
5. The method for preparing the wear-resistant large-size integrated dust removal and denitrification filter element according to claim 1, characterized in that: In the preparation of the treated functional ceramic fiber membrane material waste, the decrease rate of the denitrification efficiency of the used functional ceramic fiber membrane material waste does not exceed 60%; A 50-mesh sieve is used in the sieving; The type of catalyst in the used functional ceramic fiber membrane material waste is one of a vanadium tungsten titanium catalyst and a rare earth catalyst.
6. The method for preparing the wear-resistant large-size integrated dust removal and denitrification filter element according to claim 1, characterized in that: The preparation method of the cationic nanoparticles comprises: mixing montmorillonite and a first portion of deionized water, stirring at 50-55° C., adding a polyvinyl pyrrolidone aqueous solution, continuing stirring, centrifuging, washing the precipitate with deionized water, mixing with a second portion of deionized water, stirring at 20-40° C., adding a hexadecyltrimethylammonium bromide aqueous solution, continuing stirring, centrifuging, washing the precipitate, and drying to obtain the cationic nanoparticles; In the preparation of the cationic nanoparticles, the montmorillonite is sodium montmorillonite with a particle size of 300 nm; The weight ratio of montmorillonite to the first portion of deionized water is 40:1800-2000; The weight ratio of montmorillonite to polyvinyl pyrrolidone aqueous solution is 40:270-290; The weight ratio of montmorillonite to the second portion of deionized water is 40:1400-1700; The weight ratio of montmorillonite to the aqueous solution of hexadecyltrimethylammonium bromide is 40:600-650; The polyvinyl pyrrolidone in the polyvinyl pyrrolidone aqueous solution is polyvinyl pyrrolidone K30, with a mass concentration of 5%; The mass concentration of the aqueous solution of hexadecyltrimethylammonium bromide is 2%; The aggregate has a particle size of 0.2-1 mm and a porosity of 35-70%; The silica sol has a silicon dioxide content of 30-40% and a particle size of 10-50 nm.
7. The method for preparing the wear-resistant large-size integrated dust removal and denitrification filter element according to claim 1, characterized in that: When the catalyst type in the catalyst slurry is a vanadium-tungsten-titanium catalyst, the preparation method of the catalyst slurry is to mix titanium dioxide, ammonium metavanadate, ammonium metatungstate, ammonium metamolybdate, silica sol, ammonia water, a surfactant, anionic nanoparticles, and water to obtain a catalyst slurry; In the preparation of the catalyst slurry, the weight ratio of titanium dioxide, ammonium metavanadate, ammonium metatungstate, ammonium metamolybdate, silica sol, ammonia water, surfactant, anionic nanoparticles, and water is 70-75:13-15:9-10:7-8:6-7:18-20:10-11:10-12:90-100; The particle size of the titanium dioxide is 100 nm; The silica sol has a silicon dioxide content of 30-40% and a particle size of 10-50 nm; The mass concentration of the ammonia water is 31%; The surfactant is triethylamine.
8. The method for preparing the wear-resistant large-size integrated dust removal and denitrification filter element according to claim 7, characterized in that: When the catalyst type in the catalyst slurry is a rare earth catalyst, the preparation method of the catalyst slurry is to mix titanium dioxide, cerium nitrate, a soluble transition metal salt, silica sol, ammonia water, a surfactant, anionic nanoparticles, and water to obtain a catalyst slurry; In the preparation of the catalyst slurry, the weight ratio of titanium dioxide, cerium nitrate, soluble transition metal salt, silica sol, ammonia water, surfactant, anionic nanoparticles, and water is 70-75:15-17:33-35:7-8:20-22:8-10:10-12:120-130; The particle size of the titanium dioxide is 100 nm; The soluble transition metal salt is one or a combination of iron nitrate, manganese nitrate and copper nitrate; The silica sol has a silicon dioxide content of 30-40% and a particle size of 10-50 nm; The mass concentration of the ammonia water is 31%; The surfactant is triethylamine.
9. The method for preparing the wear-resistant large-size integrated dust removal and denitrification filter element according to claim 8, characterized in that: The preparation method of the anionic nanoparticles in the preparation of the catalyst slurry is as follows: montmorillonite and a first portion of deionized water are mixed, stirred at 50-55° C., a polyvinyl pyrrolidone aqueous solution is added, the stirring is continued, centrifuged, the precipitate is washed, and the mixture is mixed with a second portion of deionized water, stirred at 20-40° C., a sodium dodecylbenzene sulfonate aqueous solution is added, the stirring is continued, centrifuged, the precipitate is washed, and then dried to obtain the anionic nanoparticles; In the preparation of the anion nanoparticles in the catalyst slurry, the montmorillonite is sodium montmorillonite with a particle size of 300 nm; The weight ratio of montmorillonite to the first portion of deionized water is 40:1800-2000; The weight ratio of montmorillonite to polyvinyl pyrrolidone aqueous solution is 40:270-290; The weight ratio of montmorillonite to the second portion of deionized water is 40:1400-1700; The weight ratio of montmorillonite to the aqueous solution of sodium dodecylbenzene sulfonate is 40:900-1000; The polyvinyl pyrrolidone in the polyvinyl pyrrolidone aqueous solution is polyvinyl pyrrolidone K30, with a mass concentration of 5%; The mass concentration of the sodium dodecylbenzenesulfonate aqueous solution is 1%.
Citation Information
Cited By
Integrated ceramic filter tube as well as preparation method and application thereof
CN122098100A